Iodine geodynamics and plant availability - Humphrey, Olivier S. (2019)
Iodine is an essential micronutrient for human health. However, approximately 1.9 billion people worldwide are at risk of developing an iodine deficiency disorder. The uptake of iodine by crops and subsequent consumption can be a vital component of dietary intake: further understanding of soil and crop iodine dynamics will determine the sustainability of iodine phytofortification.